Nesting behavior of Gorilla gorilla diehli at Kagwene Mountain, Cameroon: implications for assessing group size and density - Sunderland-Groves, J.; Ekinde, A.; Mboh, H. (2009)
We recorded nesting data at 569 fresh night nest sites, comprising 7032 individual nests, of Cross River gorillas inhabiting the Kagwene Mountain in western Cameroon. The mean night nest group size was 12.4. Overall, 55% of night nests were constructed on the ground and 45% in trees. Significantly more arboreal nests were constructed in the wet season (69%), vs. the dry season (19%). Day nest construction was common at Kagwene (n = 260 nest sites, mean nest group size = 5.98) and we encountered significantly more day nest sites in the wet season. Nest site reuse was also common (35%), though not related to season. Our results of nesting habits concur with those from other western gorilla studies, in which rainfall influences arboreal nesting. However, we encountered wet season arboreal nesting, day nest construction, and overall nest site reuse more frequently than reported for other sites. Our observations have considerable implications when estimating group size and density using traditional nest count data. The gorillas at Kagwene inhabit the highest altitudinal range of all Cross River gorilla subpopulations and rainfall is also high; therefore other subpopulations may demonstrate different nesting characteristics. However, one should consider our findings when attempting to estimate Cross River gorilla density at other localities through nest site data.